Struggle on the Nile - Salem, Atef; Kalileo; Sharif, Omar; Abaza, Rouchdi; Rostom, Hind
The set-up for the film involves a group of old men in Luxor who sense the changes coming to their livelihood with the construction of the high dam in Aswan. They sell their boats and want to invest in a barge. To this end they employ two young men, cousins (Omar Sherif and Rushdi Abaza), to sail north to Cairo and buy that barge. Of course this means safeguarding the small bag filled with 6,000 Egyptian pounds (a fortune). Some jealous villagers learn about this plan - and the large purse of money - and set about trying to steal the money and foil the plans. The most sustained effort to do that involves a duplicitous women (Hind Rostam ... a Marilyn Monroe-type bombshell) who feigns helplessness and winds her way into the hearts of the two cousins. Tour de force performance by Omar Sharif, Rushdi Abaza and Hind Rostom and directed by Atef Salem. [www.tulumba.com]
Keywords: DVD-Video